Studi Komparasi Strategi Snowball Throwing DanReading Guide Terhadap Hasil Belajar Ipa SiswaKelas V SD Negeri Srimulyo I Tahun 2015/2016 - Sulastri, Sulastri; , Drs. Mulyadi S. K., SH.,M.Pd (2016)
Sulastri / A510120011. COMPARISON STUDY OF STRATEGY SNOWBALL THROWING AND READING GUIDE LEARNING OUTCOMES OF IPA CLASS V SD NEGERI SRIMULYO I YEAR 2015/2016. Essay. Primary School Teacher Education Program, The Faculty of Education, University of Muhammadiyah Surakarta. April, 2016. This study aims to determine: (1) the difference in strategy use Snowball Throwing and Reading Guide on learning outcomes science class V students of SD Negeri Srimulyo I Year 2015/2016. (2) a better strategy between strategy Snowball Throwing and Reading Guide on learning outcomes science class V students SD Negeri Srimulyo I year 2015/2016. This study included a quantitative study with an experimental model. The research subject grade V students SD Negeri Srimulyo I. The data collection technique using the technique of tests and documentation. Test instrument is used to test the validity and reliability testing. Data analysis technique using the t-test technique which preceded the prerequisite test analysis, the test for normality using Liliefors. Based on data analysis with a significance level of 5% was obtained t_hitung> t_tabel, ie -2.838> -1.997. And obtained the average value of learning outcomes IPA using Snowball Throwing and strategy Reading Guide that is 66.81  75,97. The conclusion of this study were (1) there is a difference between the using a strategy Snowball Throwing and strategy Reading Guide on learning outcomes science class V students SD Negeri Srimulyo I Year 2015/2016.(2) strategy Reading Guide better than the strategy of Snowball Throwing the learning outcomes of science class V students SD Negeri Srimulyo I Year 2015/2016. Keywords: Science Learning Outcomes, Strategy Snowball Throwing, Strategy Reading Guide